COMPARATIVE EFFICACY OF MOMORDICA CHARANTIA LEAF AND SEED RACTS AGAINST THE FILARIAL VECTOR CULEX QUINQUEFASCIATUS - C.A ANNAPOORANI.,; K. MANIMEGALAI., (International Journal of Pharma and Bio Sciences, 2013)
A comparative study using Momordica charantia leaf and seed extract on the fourth instar larvae of Culex quinquefaciatus. A maximum mortality (100%) was observed in petroleum ether leaf extract at 72hr and in seed extracts minimum larval mortality was observed in petroleum ether, chloroform and ethanol extracts.